LEGAL REVIEW OF THE NEUTRALITY OF STATE CIVIL APPARATUS IN ELECTIONS - Haptoro, Dyanzah Aji; Fadlurrohim, Rifqi; Siagian, Afny Azzahra; Khanza, Ghinaya Zalfa; Iskandar, Stevri (Ilmu Hukum Prima (IHP), 2025)
This study examines the legal aspects of Civil Service Neutrality in Indonesian general elections. Civil service neutrality represents a fundamental principle in democratic governance with integrity. Through a normative juridical approach, this research analyzes the regulatory framework governing civil servant neutrality, common forms of violations, and the effectiveness of existing supervision mechanisms and sanctions. The findings indicate that despite Indonesia having comprehensive legislation regarding civil service neutrality, its implementation still faces various challenges, including diverse interpretations of the boundaries of civil servants' political activities, weak law enforcement, and lack of awareness and understanding among civil servants themselves. This research recommends strengthening collaborative oversight mechanisms between institutions, clarifying the boundaries and definitions of civil servants' political activities, and enhancing education and socialization regarding civil service ethics in the context of electoral democracy.